The Role of Achievment Motivation in Improving Cognitive Learning Outcomes of Creative Products and Entrepneurship of SMK Negeri 2 Kupang Students - Yuliati Yuliati; Agapitus H Kaluge; Kletus Erom; Vincent Gaspersz (Universitas Muhammadiyah Enrekang, 2024)
The purpose of the study was to prove the role of achievement motivation in improving entrepreneurship learning outcomes of students of SMK Negeri 2 Kupang. This research is a quasi-experimental research with Nonequaivalent Control Group Design, which was conducted on a group of 20 students with high achievement motivation and a group of 19 low achievement motivation students in class XI TKR 1 SMK Negeri 2 Kupang, 2023. The analysis requirement test was carried out with normality and homogeneity tests. Data analysis techniques using t test analysis. The results showed that: 1) Student groups with high achievement motivation have the character of trying to do tasks optimally and on time, persistent, like competition and visionary. 2) The group of students with high achievement motivation has higher learning outcomes (mean 75.15) compared to the group of students with low achievement motivation (mean 68.2). Therefore, achievement motivation has a role in improving the cognitive learning outcomes of creative products and entrepreneurship of students of SMK Negeri 2 Kupang